2022
DOI: 10.3390/biomedicines10123117
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome and Its Implication in the Mucosal Digestive Disorders

Abstract: The gastrointestinal (GI) tract is one of the most studied compartments of the human body as it hosts the largest microbial community including trillions of germs. The relationship between the human and its associated flora is complex, as the microbiome plays an important role in nutrition, metabolism and immune function. With a dynamic composition, influenced by many intrinsic and extrinsic factors, there is an equilibrium maintained in the composition of GI microbiota, translated as “eubiosis”. Any disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 125 publications
0
20
0
Order By: Relevance
“…The human gut microbiome is considered to be an organ on its own with major interactions within the human organism, playing an active role in various immunological, neuronal, metabolic and endocrine responses [ 13 ]. The highest concentration and diversity of microorganisms from the human body lies in the gastrointestinal tract, consisting of more than 500 distinct species of bacteria, viruses, fungi and protozoa [ 14 , 15 ].…”
Section: Gut-associated Microbiome Composition and Function In Health...mentioning
confidence: 99%
See 1 more Smart Citation
“…The human gut microbiome is considered to be an organ on its own with major interactions within the human organism, playing an active role in various immunological, neuronal, metabolic and endocrine responses [ 13 ]. The highest concentration and diversity of microorganisms from the human body lies in the gastrointestinal tract, consisting of more than 500 distinct species of bacteria, viruses, fungi and protozoa [ 14 , 15 ].…”
Section: Gut-associated Microbiome Composition and Function In Health...mentioning
confidence: 99%
“…The highest concentration and diversity of microorganisms from the human body lies in the gastrointestinal tract, consisting of more than 500 distinct species of bacteria, viruses, fungi and protozoa [ 14 , 15 ]. The GI microbiota are represented by five primary bacterial phyla: the Firmicutes (synonym Bacillota ) and Bacteroides (synonym Bacteroidota ) phyla predominate the microbiome and represent more than 90% of total bacterial communities, while the Proteobacteria (synonym Pseudomonadota) , Actinobacteria (synonym Actinomycetota ), and Verrucomicrobia phyla are represented in smaller proportions [ 13 , 16 ]. Although the Bacillota phylum consists of more than 200 different genera such as Bacillus , Lactobacillus , Enterococcus , Ruminococcus and Clostridium , and the Clostridium genus represents 95% of the phylum.…”
Section: Gut-associated Microbiome Composition and Function In Health...mentioning
confidence: 99%
“…Regarding the pediatric consequences of cesarean section, several studies concluded that cesarean section is a risk factor for respiratory tract infections, asthma, obesity, and neurological disorders in children [ 45 ]. Current studies consider early alteration of the human microbiome to play an important role in the onset and progression of several diseases by modulating important metabolic and immunomodulatory processes [ 99 , 100 ]. Depending on the delivery mode, quantitative and qualitative differences have been found in newborns’ intestinal microflora [ 45 ].…”
Section: The Impact Of Cesarean On the Fetusmentioning
confidence: 99%
“…Depending on the delivery mode, quantitative and qualitative differences have been found in newborns’ intestinal microflora [ 45 ]. Infants born through the birth canal share their mothers’ vaginal and fecal flora, while those delivered through cesarean section have a microbiota similar to their mothers’ skin and to the surrounding environment [ 100 ].…”
Section: The Impact Of Cesarean On the Fetusmentioning
confidence: 99%
“…Inflammatory intestinal diseases (Crohn's disease and ulcerative colitis) have unknown aetiologies and a marked incidence in many developed countries. Numerous studies have suggested the important role of intestinal microbiota in the pathogenesis of inflammatory bowel disease (Bozomitu et al, 2022;Chen et al, 2014). The intestinal dysbiosis in patients with inflammatory bowel disease involve a decrease in the intestinal microflora of Firmicutes and Bacteroides.…”
Section: Dysbiosis Associated With Other Pathologiesmentioning
confidence: 99%